A tactile sensor translating texture and sliding motion information into electrical pulses1. Issue 24 (28th June 2015) - Liao, Zhipeng; Liu, Weihua; Wu, You; Zhang, Chen; Zhang, Yan; Wang, Xiaoli; Li, Xin
<x xml:space="preserve">Abstract</x> Translating texture and sliding motion information into electric pulses.